Leadership in the context of the management process in Eastern Europe: Lithuania and Poland cases. A comparative study - Stańczyk-Hugiet, Ewa; Stańczyk, Sylwia (Przywództwo w kontekście procesu zarządzania w Europie Wschodniej: przypadek Litwy i Polski. Analiza porównawcza, 2011)
The purpose of the present article is to present and attempt to explain the management process from the perspective of leadership. The article is based on the empirical studies carried out in Poland and Lithuania on the managers’ population. It also indicates the results of the research in this area carried out worldwide. The results of the studies give grounds to draw interesting comparisons and conclusions as to the attitudes and the behavior of the managers in these two countries
Ekonomia = Economics, 2011, Nr 2 (14), s. 309-320
Keywords: leadership; Poland; Lithuania